Iowa Birdline update, January 18, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for January 18, 1993. Highlights of the update include sightings of Carolina Wrens and the continued presence of the two Townsend's Solitaires, Long-tailed Duck, Trumpeter Swans and Iceland Gull. Also included are handwritten notes for the next week's update with sightings of Snow Bunting flocks west of Rock Falls and a red phase Eastern Screech Owl at Hickory Hill Park. Epson - sheet feed/flatbed